Behçet's syndrome / AIDS / cerebral toxoplasmosis: an unusual association - Chahade, Wiliam Habib; Soares, Virgina de Faria; Guimarães, Thais; Berbert, Suzi Osana Teixeira; Szwarc, Isac Szarf; Levi, Guido Carlos (São Paulo Medical Journal, 1994)
Few cases of AIDS associated to manifestations suggesting Behçet's syndrome have been reported. This case is of a young married woman who presented, during a period of 7 years, clinical manifestations consistent with the late diagnosis of Behçet's syndrome, when she developed recurrent lymphomonocytic meningoencephalitis. At this time, she was found to be infected by HIV-1. Immunosupressive doses of glucocorticoid produced an unsatisfactory response and she evolved to death due to CNS toxoplasmosis. The latter diagnosis was presumed on the basis of magnetic resonance imaging findings and proved by necropsy after her third hospital stay. One of the factors hindering the appropriate diagnosis was the low level of CD4 and the CD4/CD8 ratio, sometimes observed in active Behçet's syndrome and higher than those observed in patients with this severe opportunistic infection. No information about the exact period of time she had been infected with HIV-1 is available. So, we do not know whether both diseases were overlor, if the patient, infected by HIV-1, developed an unusual clinical feature consistent with Behçet's Behçet's syndrome, and subsequently evolved to AIDS.